Entanglement Explained by Sequencing Satisfies Lack of Trajectory and The Holographic Principle - Khumalo, Bhekuzulu (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The implications of entanglement have scared many, but if we use all we understand about existence sequencing is probably the answer given probable experiments that we should have the technology to do within the next 5 years. The simpler the easier to understand. This paper is in the tradition of thought experiments, not all have access for modern technology, a thought of the mind, given that we are further introducing algorithms into not only physics but life in general, sequencing is merely an algorithm.